MOTIVASI NEGARA DALAM MENENTUKAN ANGGARAN PERTAHANAN - Kennedy, Posma Sariguna Johnson (Universitas Kristen Indonesia, 2017)
There is not a general theory capable of explaining how the defense budget should be formulated. However, through the theory of economic behavior, estimation can be performed. The defense budget is generally a complex tug of war between the political, economic, social, military, and technology. This study is a qualitative research by reviewing a variety of literature dealing with the problem of motivation of state defense budget. Despite many obstacles, the estimate remains to be done, due to the projected budget in the long term, is an important instrument for a wide range of organizations plan to set goals and overcome the various problems that exist now and in the future. It also estimates the military budget is essential for economic operators, the parties concerned with all economic activity because the rise and fall of the military budget in general have an impact on the economy.